PENGARUH AKTIVITAS FISIK TERHADAP PRODUKSI ASI PADA IBU MENYUSUI - Berkat Turil Bewamati Zebua; Dominggos Simanjuntak; Arif Sianipar; Muhammad Raihan Aditya; Nurhamida Sari Siregar; Randi kurniawan (Jurnal Keluarga Sehat Sejahtera, 2026)
Exclusive breastfeeding (ASI) for the first six months of a baby’s life is a fundamentalhealth intervention recommended by the World Health Organization (WHO). Thesuccess of the breastfeeding process is crucial for the optimal health and developmentof the infant, as breast milk not only provides complete nutrition but also essentialantibodies. Breast milk production is influenced by various factors, includingphysiological conditions, such as the balance of the hormones prolactin and oxytocin,as well as psychological factors like stress and fatigue. Among these various factors,physical activity performed by mothers during the breastfeeding period plays as significant role, although the perception regarding its effect remains diverse among thepublic. This study aims to comprehensively describe the influence of physical activityon breast milk production in nursing mothers. The method used is descriptive qualitative through a literature review of various relevant scientific books and journals.The review results indicate that light to moderate intensity physical activity significantly supports the increase in breast milk production. This benefit is achieved through several mechanisms, including improved blood circulation throughout the body, including the breasts, which optimizes the supply of oxygen and nutrients to the mammary glands. Furthermore, regular physical activity helps balance the hormones prolactin (which stimulates milk synthesis) and oxytocin (which plays a role in the milk ejection reflex). From a psychological perspective, physical activity is proven effective in reducing levels of stress, anxiety, and postpartum depression. This stable psychological condition is crucial because stress is known to inhibit breast milk production. Conversely, excessive physical activity can have a negative impact by causing exhaustion, dehydration, and a reduction in energy reserves, which can ultimately decrease the volume of breast milk. Therefore, nursing mothers are advised to choose physical activities such as walking, light aerobics, or yoga, and to adjust the intensity to their body's capacity. Education and guidance from health professionals are needed to ensure that nursing mothers understand the benefits and limitations of physical activity correctly.